2004
DOI: 10.1111/j.1469-0691.2004.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in Greece: a changing profile. Epidemiological, microbiological and therapeutic data

Abstract: The epidemiology, and clinical and microbiological spectrum, of infective endocarditis (IE) in Greece was analysed in a prospective 4-year study in a tertiary hospital and a heart surgery centre in Athens. In total, 101 cases of IE (71 men, 30 women, aged 54.4 +/- 17.1 years) were studied, with a follow-up period of 3 months. Seventy-seven cases were definite and 24 possible; 59 involved native valves (native valve endocarditis; NVE), 31 prosthetic valves (prosthetic valve endocarditis; PVE), of which nine wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 26 publications
11
44
0
12
Order By: Relevance
“…Although IE patients included in the present study manifested with a wide range of signs and symptoms, in consistent with the previous studies, [7,8,[11][12][13][14][15][16][17][18] the most common symptom was fever (86.7%), while the most common physical examination finding was murmur (88.1%). The patients who received the diagnosis of IE within the first 30 days following symptom onset accounted only for 53.8% of the study population.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although IE patients included in the present study manifested with a wide range of signs and symptoms, in consistent with the previous studies, [7,8,[11][12][13][14][15][16][17][18] the most common symptom was fever (86.7%), while the most common physical examination finding was murmur (88.1%). The patients who received the diagnosis of IE within the first 30 days following symptom onset accounted only for 53.8% of the study population.…”
Section: Discussionsupporting
confidence: 88%
“…[2] According to data collected in the Euro Heart Survey study, the mean age of patients at IE onset was 56±17 years in Europe, while a study performed in Greece, one of Turkey's neighbor countries, reported a mean age of 54±17 years. [11,12] The mean age of patients at IE onset is as low as 32 years in countries such as Tunisia and India. [13,14] Studies performed in Turkey in different time points reported the mean age at disease onset varying between 45 and 47 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of retrospective studies published during the 1990's, the oral cavity was identified to be the portal of entry of the causative microbial agent in 14-20% of cases of bacterial endocarditis (1)(2)(3), with the prevalence of bacterial endocarditis of possible oral origin in recently published series being similar to that reported in these older series (4)(5)(6).…”
Section: Introductionmentioning
confidence: 79%
“…In all, VGS are now the most frequent etiological agents in IE (54)(55)(56)(57)(58)(59)(60)(61). Moreover, in nonintravenous users, where aortic or mitral IE dominates, VGS are the major etiological agents (25,62).…”
Section: Infective Endocarditismentioning
confidence: 99%